2010
DOI: 10.5070/c7291021191
|View full text |Cite
|
Sign up to set email alerts
|

Paint by Number? How the Race and Gender of Law School Faculty Affect the First-Year Curriculum

Abstract: as well as EDP Consultant Linda Wightman; without their visionary efforts EDP would not exist and this article could not have been written. We also thank all researchers involved in data collection and analysis for EDP, and especially the many law students who participated in this project. This paper benefited from comments received during a presentation as part of the American Educational Research Association Annual Meeting in April 2007. We also thank Joel Marrero and the other editors at the Chicano-Latino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Marin (2000) additionally concluded professors need to consider their role as facilitators rather than simply as knowledge-givers, allowing students (and faculty) to learn from each other, and that faculty must work to create settings where all students are included and valued so that benefits can be realized by all. Nonetheless, Deo et al (2010) found law students differed in their assessments of faculty who incorporated diversity—many appreciated the context and felt it improved their understanding of the law, whereas others preferred it be excluded, a finding echoed and further examined in this article. Deo et al (2010) used the same data as the current study, however our study examines the effects of structural diversity in a classroom and how professors can best leverage the diversity of students’ experiences to achieve learning and democracy benefits, leading to important implications for both policy and practice.…”
Section: Review Of the Literaturementioning
confidence: 58%
See 4 more Smart Citations
“…Marin (2000) additionally concluded professors need to consider their role as facilitators rather than simply as knowledge-givers, allowing students (and faculty) to learn from each other, and that faculty must work to create settings where all students are included and valued so that benefits can be realized by all. Nonetheless, Deo et al (2010) found law students differed in their assessments of faculty who incorporated diversity—many appreciated the context and felt it improved their understanding of the law, whereas others preferred it be excluded, a finding echoed and further examined in this article. Deo et al (2010) used the same data as the current study, however our study examines the effects of structural diversity in a classroom and how professors can best leverage the diversity of students’ experiences to achieve learning and democracy benefits, leading to important implications for both policy and practice.…”
Section: Review Of the Literaturementioning
confidence: 58%
“…Nonetheless, Deo et al (2010) found law students differed in their assessments of faculty who incorporated diversity—many appreciated the context and felt it improved their understanding of the law, whereas others preferred it be excluded, a finding echoed and further examined in this article. Deo et al (2010) used the same data as the current study, however our study examines the effects of structural diversity in a classroom and how professors can best leverage the diversity of students’ experiences to achieve learning and democracy benefits, leading to important implications for both policy and practice.…”
Section: Review Of the Literaturementioning
confidence: 58%
See 3 more Smart Citations